Direct synthesis of butadiynyl-substituted pyrroles under solvent- and transition metal-free conditions1. Issue 89 (27th September 2015) - Tomilin, Denis N.; Pigulski, Bartłomiej; Gulia, Nurbey; Arendt, Agata; Sobenina, Lyubov N.; Mikhaleva, Al'bina I.; Szafert, Sławomir; Trofimov, Boris A.
<x xml:space="preserve">Abstract</x> The work describes a convenient and highly efficient C–H butadiynylation of substituted pyrroles under mild and solvent-free conditions.